Application of the Inverse Finite Element Approach for the Fast Simulation of Tube Hydroforming. (2016) - Chebbah, Mohamed-Saïd; Hebbir, Nacer; Kanit, Toufik; Dehimi, Sara
Abstract: In this paper we present an inverse finite element approach for the simulation of anisotropic tube hydroforming operation. This method exploits the knowledge of the final part shape, by starting from this later we search for the nodal positions in the initial cylindrical tube which verify the equilibrium of the final part. We propose a geometrical initial solution allows avoiding the problem of vertical walls and reverse taper. Two numerical applications concerning the hydroforming of T and Y-shaped tubes made from welded low carbon steel AISI 1008-galvanized, using the flow stress data obtained from bulge test have been utilized to validate the method. Verifications of the obtained results have been carried out using the classical explicit dynamic incremental approach (EDIA) by ABAQUS ® commercial code to show the efficiency of our approach.